A cross-sectional study to assess the drug utilization pattern and pharmacotherapeutic adherence among patients with schizophrenia and quality of life of patient’s caregiver in a tertiary care teaching hospital - Parikh, Honshil V.; Vyas, Bhavesh M.; Dumra, Gurusharan H. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Schizophrenia is a chronic severe psychiatric illness affecting nearly 0.4 to 1.4% of people in India. Many newer anti-psychotic drugs are used now-a-days in schizophrenia. Poor adherence to the treatment given to patients of schizophrenia is observed very often. Although, the quality of life of schizophrenia patients is very much compromised; at the same time, quality of life of the caregiver is also compromised. Methods: A cross-sectional Observational study was conducted among patients already diagnosed with Schizophrenia and on treatment, after ethical approval. Data relevant to study variables was collected in a pre-designed case record form. Evaluation of drug utilization pattern was done by WHO core drug prescribing indicators. Medication adherence was assessed through modified Morisky scale. Quality of life of relative or caregiver was assessed through WHO-QOL BREF questionnaire scale. Results: Patients of 18 years and above were enrolled. Among them, average age was 35.8±5.5 years. In my study, female patients were 64.7% and male patients were 35.3%. Average number of drugs per prescription was 3.8. Drugs prescribed by generic name were around 86.2%. Around 56.9% of drugs were prescribed from national list of essential medicines. Atypical antipsychotics were prescribed in 32% of all prescriptions for Schizophrenia; Whereas Benzodiazepines were prescribed in 19% of all prescriptions. Average Medication adherence score using MMS scale was 3.7±2.2. Patients with high adherence to the medications prescribed were nearly 71% and patients with low adherence to the medications prescribed were 29%. Mean total WHOQOL-BREF score was 75.2±6.5 out of 120. Conclusions: Most prescribed class of drugs was atypical anti-psychotics. Pharmacotherapeutic adherence among patients with schizophrenia was relatively high. Quality of life of patients’ relative or caregiver was impaired to some extent, more impaired in physical health and social relationships domain.